UJI ANGKA LEMPENG TOTAL dan ANGKA KAPANG KHAMIR EKSTRAK BUAH OKRA (Abelmoschus esculentus L.) - Chandra, Pra Panca Bayu (Parapemikir : Jurnal Ilmiah Farmasi, 2024)
Okra fruit is an excellent plant used as a raw material for traditional medicine. Okra fruit as a raw material for medicine must go through a quality parameter testing process to make it safe to use. One of the extract quality parameters is the Total Plate Number (ALT) and Yeast Mold Number (AKK). This study aims to evaluate the suitability of microbial contamination and yeast mold in 70% ethanol extract of okra fruit against applicable regulations. Extraction of okra fruit by maceration method with 70% ethanol solvent for 5 days with a ratio of 1:10. The results obtained from 70% ethanol extract of okra fruit have organoleptic characteristics of thick, blackish brown color, typical okra odor and sour bitter taste. typical. The ALT and AKK values in the 70% ethanol extract of okra fruit are 0, fulfilling the safety and quality requirements for traditional medicines.